Re-reading Luke’s community : The ambivalence of location and identification from a social identity complexity lens - Marevesa, Tobias; Mavengano-Marevesa, Esther (Stellenbosch Theological Journal, 2022)
This article interrogates and examines the community of Luke and the ambivalence of the location, composition, and identity problematics issues through the Social Identity Complexity perspective (SIC hereafter). The fundamental questions which this article seeks to grapple with are: Was the community of Luke Corinth, Ephesus, or Antioch? Which social boundary markers were erected among the multiple and complex social groups within the community of Luke? The arguments in this article are framed by insights from the Social Identity Complexity Theory which was developed by Roccas and Brewer (2002). The SIC perspective is useful and relevant in re-reading and problematizing identity markers of the numerous social groups within the community of Luke. The article also explores a significant aspect of the troubled composition of the social groups in the community of Luke. This study established that there are multiple and complex social identity formations in Luke's community. Furthermore, the social identities of the members of the Lukan community were fluid, nuanced, and troubled, as highlighted in the discussion in this article.